ABOUT A TWIN SOLUTION OF THE VEKUA EQUATION - Brsakoska, Slagjana (Matematichki Bilten, 2016)
In the paper main object of research is the Vekua equation. Two types of functions are found that are strongly connected to each other because it will be proven that if one of them is a solution of the Vekua equation, so will be the other one with a corresponding condition. Three different cases are considered.